Spatial-temporal Pattern and Influencing Factors of Listed Enterprises in China’s Strategic Emerging Industries - Peichao Dai (International Journal of Industrial Engineering and Engineering Management, 2025)
This study analyzes the structure and spatial distribution of listed companies in China's strategic emerging industries (SEIs) from 2010 to 2021, using a quantitative approach. An industrial diversity index is created to assess provincial structures, and spatial agglomeration is examined through a spatial autocorrelation model. The distribution is visualized with kernel density estimation (KDE), and migration patterns of the gravity center are tracked. The key findings are as follows: (1) Significant regional disparities in SEI development exist, with greater diversity in the Yangtze River Delta (YRD), Beijing-Tianjin-Hebei (BTH), and the Pearl River Delta (PRD) compared to other regions; (2) The distribution shows strong positive spatial autocorrelation, indicating a pronounced agglomeration effect; (3) The spatial center of gravity primarily shifts within Central China; (4) The distribution follows a pattern of decreasing concentration from the eastern coastal areas to the western inland regions, with scattered presence in the central and northeastern regions; (5) Key factors such as economic development (DN values), policy support, R&D investments, passenger turnover, and technology market activity play a significant role in shaping the number of listed companies in each region. This analysis offers valuable insights for policymakers aiming to guide regional industrial development.